Gender equality and female incarceration: Evidence from global and regional analyses - Chu, Doris C. (Criminology & criminal justice, 2025)
This article examines the nature of female1 incarceration patterns globally and regionally in relation to societal gender equality using cross-national analysis of 138 countries. Importantly, our analysis uses a conceptually innovative gender-specific indicator (the World Economic Forum’s Global Gender Gap Index) to determine relative levels of gender equality. Results of our study show that globally, countries with a narrower gender gap in economic participation made higher use of female incarceration, and this was also the case in the Asian and European regions. Countries with a narrower gap in political empowerment were found to have lower female incarceration rates globally and in the European region, but have higher female incarceration rates in the African region. Limitations are noted and suggestions for future studies are made.